Secondary Metabolite Test for Heterotrophic Bacteria from Siak River Estuary Against Pathogenic Bacteria - Adolf Hiskia Nainggolan; Feliatra Feliatra; Andi Dahliaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Secondary metabolites are a molecule or product of metabolites produced by the metabolic processes of microorganisms where the metabolite products are not a basic necessity of living microorganisms and for growth, but secondary metabolites can also function as emergency nutrients to survive. Marine bacteria including heterotrophic bacteria are capable of producing secondary metabolites. This study aims to determine the ability of secondary metabolite production of heterotrophic bacteria to inhibit the activity of pathogenic bacteria (Vibrio alginolyticus, Aeromonas hydrophila and Pseudomonas sp). In this study using the experimental method. 10 Heterotrophic bacterial isolates obtained from a collection of marine microbiology laboratories were cultured on NB media ± 3 days until the media was cloudy and harvest during stationary times, then extracted secondary metabolites from the media and shells using Etyl Acetate. The secondary metabolite extract will be tested against pathogenic bacteria (Vibrio alginolyticus, Aeromonas hydrophila and Pseudomonas sp). Based on the results of the antagonism test conducted, 10 heterotrophic bacterial isolates were able to inhibit the growth of all three pathogenic bacteria. Based on the antagonism test, the highest inhibitory value was Bacillus cereusspecies (KM489154.1) with an average diameter of about 10.08 mm, while the inhibition power which was classified as the lowest or categorized as moderate was found in the Bacillus safensis species (KY495152.1 ) with an average diameter of around 7.33 mm. The ability to inhibit pathogenic bacteria is suspected because this heterotrophic bacterial species produces antibiotic compounds. Keyword :Secondary metabolites, Heterotrophic Bacteria, Antagonism test